Konflik Komunal Mengatasnamakan Agama di Indonesia: Analisis terhadap Konflik Ahmadiyah dalam Pemberitaan Media, 2005-2011 - Hasan, Bakhtiar; Mursalin, Ayub (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2011)
The article offers a fresh perspective to analyze the conflict through observation of media coverage, proposing that through this close observation, the form, factors and motives of conflict can be easily identified. Through its observation, this paper records that the clash between Ahmadiyyah and other religious groups has predominated social conflict in Indonesia since 2005 until 2011. It argues that the conflict persistence is due to a weak law enforcement. The state is deemed to be failed to protect the minority group against the violent acts of other religious groups and it is this failure that this artcile associates with the escalation and development of the conflict.